Neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio in chronic periodontitis before and after nonsurgical therapy - Acharya, Anirudh Balakrishna (J Indian Soc Periodontol, 2019)
BACKGROUND: Various biomarkers have been evaluated for understanding the systemic inflammatory response (SIR) to periodontitis. Hematological markers have been reported to be useful biomarkers in a variety of diseases, including periodontal diseases. The role of neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) in periodontitis and their possible role in the SIR are not extensively documented. Therefore, this study assessed NLR and PLR in chronic periodontitis (CP) patients before and after periodontal treatment, which to the best of knowledge has not been reported in the literature. MATERIALS AND METHODS: Sixty participants were grouped as systemically and periodontally healthy (H) (n = 30) and with CP (n = 30). Plaque index, gingival index, probing pocket depth, clinical attachment loss, leukocyte counts, platelet (PLT) counts, NLR, and PLR were estimated at baseline and also after treatment in the CP group. NLR was calculated as total neutrophil count/absolute lymphocyte count, and PLR was calculated as total PLT count/absolute lymphocyte count. The data were statistically analyzed. RESULTS: Periodontal parameters differed significantly between groups H and CP at baseline and posttreatment. A pair-wise comparison of NLR and PLR between CP patients at baseline and posttreatment was significant. Correlation analyses were not remarkable. Receiver operating characteristics analyses provided significant NLR and PLR predictive cutoff values to differentiate between CP patients at baseline and posttreatment. CONCLUSION: NLR and PLR may serve as potential biomarkers of the SIR to CP to bridge the association between periodontal and systemic conditions.